Anterior Thoracolumbar Fixation for Management of Thoracolumbar Spine Injury - Sahoo, PK; Singh, P; Bhatoe, HS; Murthy, TVSP; Sandhu, K; Chaturvedi, A (Indian Journal of Neurotrauma, 2004)
A retrospective analysis was carried for sixty patients with thoracolumbar spine injury operated during Jan 2001 to Dec 2003. Fifty (84%) were male and ten were female patients. Thirty six (60%) sustained injury by vehicular accident and 24 (40%) due to fall, ejection and obstacle crossing. There were four patients with associated head injury, seven with extremity, four with chest and two patients with abdominal injury. All patients presented with features of spinal cord/cauda equina injury and evaluated with Frankel’s neurological grade at admission. Eight patients presented with grade ‘A’, two grade ‘B’, thirty six grade ‘C’, fourteen grade ‘D’ neurological deficit as per Frankel’s classification. Plain radiography, Computerised Tomography (CT) scan, and Magnetic Resonance Imaging (MRI) of thoracolumbar spine revealed fracture L1 in 32, D12 in 14, D11 in 07, L2 in 07. Corpectomy + bone grafting in 06; corpectomy + bone grafting + plating in 07; corpectomy, cage placement in 07; corpectomy, cage placement + plating in 40, were carried out. Outcome was evaluated at two months, six months and one year in Frankel’s grade. The outcome was Frankel’s ‘A’ 08, Frankel’s ‘B’ 02, Frankel’s ‘D’ 23 and Frankel’s ‘E’ 27. Ten patients did not show any recovery. There was wound infection in two, mal-alignment of cage in two and lateral placement screws were found in two patients. Revision surgery was not carried out, as the patients were stable. The implants were in position during post-operative follow up. The study revealed, there was good reduction, decompression and stabilisation in all patients. The patients were mobilised early with external support after spinal stabilisation. Patients with incomplete spinal cord injury showed excellent to good recovery and patients with initial Frankel’s ‘A’ & ‘B’ did not show any recovery.
Keywords: Anterior Thoracolumbar Z-Plate fixation; Corpectomy Thoracolumbar Spine injury; Titanium Cage Placement